The Role of Vegetation in The Environment - Tjahjono Samingan (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
Vegetation plogs a variety of Roles in the environment. Through the understanding of these roles, sometimes it is not necessary to directly control the wildlife population, instead, it suffices to control the plant communities upon which the development of the wildlife population depends. By understanding the roles of various plant specles, many activities could be conducted without creating pollution and damaging our environment. Favorable effects could be obtained when we are ignorant or diregarded the roles of the plants in the environment.